Dose–response association of handgrip strength and risk of depression: a longitudinal study of 115 601 older adults from 24 countries. (March 2023) - López-Bueno, Rubén; Calatayud, Joaquín; Andersen, Lars Louis; Casaña, José; Koyanagi, Ai; del Pozo Cruz, Borja; Smith, Lee
Abstract : Background: Prior research has solely focused on the association between handgrip strength and risk of depression in single countries or general populations, but more knowledge is required from wider-spread cohorts and target populations. Aims: This study aimed to investigate the association between handgrip strength and risk of depression using repeated measures in adults aged 50 years and over. Method: Data on handgrip strength and risk of depression were retrieved from the Survey of Health, Ageing and Retirement in Europe (SHARE) waves 1, 2, 4, 5, 6 and 7, using a hand dynamometer (Smedley, S Dynamometer, TTM) and the EURO-D 12-item scale, respectively. Time-varying exposure and covariates were modelled using both Cox regression and restricted cubic splines. Results: A total of 115 601 participants (mean age 64.3 years (s.d. = 9.9), 54.3% women) were followed-up for a median of 7.3 years (interquartile range: 3.9–11.8) and 792 459 person-years. During this period, 30 208 (26.1%) participants experienced a risk of depression. When modelled as a continuous variable, we observed an inverse significant association for each kg increase of handgrip strength and depression up to 40 kg in men and up to 27 kg in women. Conclusions: Being physically strong may serve as a preventive factor for depression in older adults, but this is limited up to a maximum specific threshold for men and women.